TRANSFORMATION TOWARDS A GREEN ECONOMY: LITERATURE REVIEW AND PRACTICAL IMPLICATIONS - Loso Judijanto; Al-Amin (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
This article explores the transformation towards a green economy, by reviewing literature that presents the concept, benefits and challenges faced in its implementation. The green economy is considered a solution to achieving sustainable development by reducing negative environmental impacts, improving resource efficiency and promoting inclusive economic growth. The research highlights the importance of cross-sector collaboration, technological innovation and policy change in supporting this transition. However, barriers such as limited funding, lack of awareness, and socio-cultural resistance need to be overcome through holistic and inclusive strategies. The study concludes that with multi-stakeholder support and the adoption of innovative practices, the transformation to a green economy can be achieved, delivering significant environmental and socio-economic benefits.